The Slum/Shacks Question and the Making of 21st Century Political Citizenship in Postcolonial Nairobi, Kenya and Harare, Zimbabwe - (:unkn) unknown (My University, 2011)
Our era is often described as a moment of globalization and urbanization. The two words, often used interchangeably, describe movements and concentration of populations in 'new' places often Diasporas described as centers of 'development'. At both global and local levels, the new places of development promise opportunities for progress and self realization for both national and global citizens. This paper explores the ambiguous status of urban areas as centers for progress and realization of cosmopolitan citizenship in 21st Century Africa. The discussion is based on cases from Nairobi, Kenya and Harare, Zimbabwe where post-colonial governments are under pressure to adhere to 'master plans' and elevate Nairobi and Harare to Western Capitalist models of metropolitan. The debate on slums/shacks is revisited, not just as multiple modernities, but as instrumental spaces of disrupting the nationalist project and globalization narratives. Any future work in urban centres cannot ignore the forms of modernities being developed and practiced by a category that is now commonly known as the 'urban poor'.
Keywords: African Research